Pengembangan Bahan Ajar Museologi Berbasis Museum pada pada Program Studi Sejarah Peradaban Islam UIN Fatmawati Sukarno Bengkulu - Arum Puspitasari; Maryam Maryam (Indonesian Journal of Social Science Education (IJSSE), 2023)
Learning material is one of the main elements in learning process, including at university. Especially for museology subject, in ideal, learning material not only based on theory but aslo combination betwwen theoty and practice. This purposes of this research are: 1) need analysis the depeloving learning material of museology based on museum; 2) developing museology learning material based on museum; and 3) validating museology learning material. The study was a mixed method (qualitative and quantitative) with research and development design in consists on ten steps: Information Collecting, Planning, Develop Preliminary Form a Product, Preliminary Field Testing, Main Product Revition, Main Field Testing, Operational Product Revetion, Operational Field Testing, Final Product Revition dan Dissemination and Implementation. Based on the research, the results obtained are: 1) the development of museology learning material based on museum is much needed by students and lectures at Islamic Civilization History Department because lact of availability museology learning material and to solve students difficulty in understanding learning content; 2) museology learning material developed concist of three main parst: 1) introduction; 2) contents; and 3) closing. Especially for contents, learning material concist on seven chapter: 1) museum; 2) construction, facilities, and vision and mission; 3) organization structures; 4) collections; 5) information label and education; 6) marketing, cooperation and mjseum fees; and 7) exhibition; 3) validation results show that museology learning material based on museum is proper to used with a number notes.